Characterization of proteoglycan 4 and hyaluronan composition and lubrication function of ovine synovial fluid following knee surgery. Issue 10 (30th May 2013) - Barton, Kristen I.; Ludwig, Taryn E.; Achari, Yamini; Shrive, Nigel G.; Frank, Cyril B.; Schmidt, Tannin A.
ABSTRACT The objective of this study was to determine changes in (1) proteoglycan 4 (PRG4) and hyaluronan (HA) concentration, (2) HA molecular weight (MW) distribution, and (3) cartilage boundary lubricating ability of synovial fluid (SF) from surgical sham (SHAM), anterior cruciate ligament (ACL)/medial collateral ligament (MCL) transection, and lateral meniscectomy (MEN) in a post‐knee surgery ovine model. Ovine SF (oSF) was collected at euthanization 20 weeks after surgery, with the contralateral joint serving as the non‐operative control. PRG4 and HA concentration in oSF was measured by sandwich enzyme‐linked immunosorbent assay, and HA MW distribution by agarose gel electrophoresis. Cartilage boundary lubricating ability of oSF was measured by a cartilage–cartilage friction test. PRG4 and HA concentration in SHAM, ACL/MCL, and MEN oSF were similar in comparison to the contralateral control (CTRL) oSF. The HA MW distribution in the operated oSF for all ranges were similar to the respective CTRL oSF. The kinetic coefficients of friction in operated and CTRL oSF were similar in all groups, and were significantly lower than saline. These results indicate oSF lubricant composition and function at 20 weeks post‐knee surgery were similar to contralateral CTRL, and suggest earlier time points post surgery warrant further investigation. © 2013 Orthopaedic Research Society Published by Wiley Periodicals, Inc. J Orthop Res 31:1549–1554, 2013